Isolating stem cells from skin: designing a novel highly efficient non-enzymatic approach - Bellu, E; Garroni, G; Balzano, F; Satta, R; Montesu, M A; Kralovic, M; Fedacko, J; Cruciani, S; Maioli, M (Physiological research, 2019)
Stem cells are undifferentiated elements capable to acquire a specific cellular phenotype under the influence of specific stimuli, thus being involved in tissue integrity and maintenance. In the skin tissue self-renewal and wound healing after injury is a complex process, especially in adulthood, due to the aging process and the continuous exposure to damaging agents. The importance of stem cells in regenerative medicine is well known and defining or improving their isolation methods is therefore a primary and crucial step. In the present paper we present a novel method to isolate stem cells from human skin, including the involvement of a novel medium for the maintenance and expansion of in vitro cultures. The biopsies were mechanically digested and put in culture. The migrating cells were positive selected with magnetic cell sorting, characterized by flow-cytometry analysis, and viability detected by MTT assay. Cells exhibited a mesenchymal phenotype, as demonstrated by the positive acquirement of an osteogenic or adipogenic phenotype when cultured in specific conditioned media. Taken together our results disclose a novel method for culturing and expanding stem cells from skin and pave the way for future clinical applications in tissue regeneration.
Keywords: separace buněk; Stem Cells; lidé; Skin; Cell Separation; kmenové buňky; Humans; kůže